2021
DOI: 10.1073/pnas.2102191118
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of beta-amyloid production in neurons by astrocyte-derived cholesterol

Abstract: Alzheimer’s disease (AD) is characterized by the presence of amyloid β (Aβ) plaques, tau tangles, inflammation, and loss of cognitive function. Genetic variation in a cholesterol transport protein, apolipoprotein E (apoE), is the most common genetic risk factor for sporadic AD. In vitro evidence suggests that apoE links to Aβ production through nanoscale lipid compartments (lipid clusters), but its regulation in vivo is unclear. Here, we use superresolution imaging in the mouse brain to show that apoE utilizes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
157
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(164 citation statements)
references
References 79 publications
5
157
0
2
Order By: Relevance
“…Given the strong genetic association between LOAD and lipid metabolism, LOAD can be considered a unique lipid disease. Recent evidence from several laboratories supports this concept [ 20 22 ].…”
Section: Ad As a Special Lipid Diseasementioning
confidence: 95%
“…Given the strong genetic association between LOAD and lipid metabolism, LOAD can be considered a unique lipid disease. Recent evidence from several laboratories supports this concept [ 20 22 ].…”
Section: Ad As a Special Lipid Diseasementioning
confidence: 95%
“…Reports have suggested the role of cholesterol in amyloid precursor protein (APP) processing [40,[51][52][53]; thus, cholesterol may be considered as a target for developing drugs to treat AD. Phytosterols are structurally similar to cholesterol and have been widely used to reduce blood cholesterol [54].…”
Section: β-Sitosterolmentioning
confidence: 99%
“…The accumulation of cholesterol in neurons promotes the interaction of APP with β- and γ-secretases in lipid clusters (lipid rafts) in neuronal membrane, resulting in Aβ formation ( Di Paolo and Kim, 2011 ). It was recently shown that cholesterol and apolipoprotein E (apoE) derived from astrocytes play an important role in amyloid plaque deposition through the regulation of membrane lipid raft function ( Wang et al, 2021 ). Moreover, genetic variation in apoE, a cholesterol transport protein is identified as a risk factor for late-onset AD ( Corder et al, 1993 ).…”
Section: Molecular Pathology Of Alzheimer’s Diseasementioning
confidence: 99%